DEVELOPMENT OF INTEGRATED PROCESS SAFETY MANAGEMENT SYSTEM FOR PROCESS INDUSTRIES - ABDUL AZIZ, HANIDA (2015)
Occupational Safety and Health Administration (OSHA) Process Safety Management (PSM) standard has excellent requirements that could and should prevent process accidents if industries follow the regulation as intended. However, compliance with the standard is challenging to the organization because of the broad scope and highly technical nature of OSHA PSM requirements. When converting the standard into the practices, these have led to great amount of misinterpretation and inconsistency resulting in poor PSM implementation program. The main objective of the study is to develop a system for effective PSM implementation and compliance with the regulation. In this study, integrating PSM programs based on interrelation between the elements is proposed which introduces interesting concept for implementing PSM in process industries.